(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discusses the genesis of the content of procedural and criminological theory of causality. Forensic causality theory promotes the development of practical recommendations for the establishment of a system event mechanism in the process of pre-trial investigation and the trial. In the criminal law science study of the problem of causality is conducted mainly in the aspect of the solution to the question of the relationship between socially dangerous act and the result of the onset of criminal and refers to the characteristic elements of the offense. The article proves the possibility of solving modern problems of regulation of investigatory actions through the use of advanced science and fundamental development of outstanding scientists. In the present case, each needs a special approach, aimed primarily at identifying the procedural and criminological theory of causality. Key words: causality, forensic causality theory, the proof, the principles of causality.